A magnetotelluric instrument for probing the interiors of Europa and other worlds. Issue 4 (15th August 2021) - Grimm, Robert; Nguyen, Ton; Persyn, Steve; Phillips, Mark; Stillman, David; Taylor, Tim; Delory, Greg; Turin, Paul; Espley, Jared; Gruesbeck, Jacob; Sheppard, Dave
Abstract: One objective of a lander mission to Jupiter's icy moon Europa is to detect liquid water within 30 km as well as characterizing the subsurface ocean. In order to satisfy this objective, water within the ice shell must also be identified. Inductive electromagnetic (EM) methods are optimal for water detection on Europa because even a small fraction of dissolved salts will make water orders of magnitude more electrically conductive than the ice shell. Compared to induction studies by the Galileo spacecraft, measurements of higher-frequency ambient EM fields are necessary to resolve the shallower depths of intrashell water. Although these fields have been mostly characterized by prior missions, their unknown source structures and plasma properties do not allow EM sounding using a single surface magnetometer or the orbit-to-surface magnetic transfer function, respectively. Instead, broadband EM sounding can be accomplished from a single surface station using the magnetotelluric (MT) method, which measures horizontal electric fields as well as the three-component magnetic field. We have developed a prototype Europa Magnetotelluric Sounder (EMS) to meet the measurement requirements in the relevant thermal, vacuum, and radiation environment. EMS comprises central electronics, a fluxgate magnetometer on a mast, and three ballistically deployed electrodes to measure differences in surface electric potential. In this paper, we describe EMS development and testing as well as providing supporting information on the concept of operations and calculations on water detectability. EMS can uniquely determine the occurrence of intrashell water on Europa, providing important constraints on habitability.